2009
DOI: 10.1016/j.foodres.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical interesterification on physicochemical properties of blends of palm stearin and palm olein

Abstract: a b s t r a c tChemical interesterification is an important technological option for the production of fats targeting commercial applications. Fat blends, formulated by binary blends of palm stearin and palm olein in different ratios, were subjected to chemical interesterification. The following determinations, before and after the interesterification reactions, were done: fatty acid composition, softening point, melting point, solid fat content and consistency. For the analytical responses a multiple regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 27 publications
1
4
0
5
Order By: Relevance
“…This was consistent with previous report (Borhan et al 2011). Karabulut et al (2004) and Soares et al (2009) suggested that the changes of melting point after interesterification might be affected by the length of fatty acids chain, the position and types of fatty acid in glycerol molecule, degree of unsaturation, trans fatty acid content and composition and species of TAGs during reactions. During the interesterification, fatty acids had rearranged in glycerol molecules at random and lead to the reduction of high melting point triacylglycerols, especially SSS (Table 2).…”
Section: Melting Point Determination and Solid Fat Contentsupporting
confidence: 93%
“…This was consistent with previous report (Borhan et al 2011). Karabulut et al (2004) and Soares et al (2009) suggested that the changes of melting point after interesterification might be affected by the length of fatty acids chain, the position and types of fatty acid in glycerol molecule, degree of unsaturation, trans fatty acid content and composition and species of TAGs during reactions. During the interesterification, fatty acids had rearranged in glycerol molecules at random and lead to the reduction of high melting point triacylglycerols, especially SSS (Table 2).…”
Section: Melting Point Determination and Solid Fat Contentsupporting
confidence: 93%
“…In fact, fats with high IV and high levels of and polyunsaturated and monounsaturated fatty acids are healthier for human nutrition (Andreia Schäfer De Martini Soares et al . ). All the blends contained linoleic and oleic acids more than 30.5 and 22.8%, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…All samples were carried out in triplicate and average of 3 measurements was used for data analysis. A multiple regression model was performed on the analytical response (SFC) according to Hare (1974); Andreia Schäfer De Martini Soares and others (2009); Silva and others (2009) represented by the following linear equation: where y is the variable and β are the coefficients generated by multiple regressions, and x is the proportion of the components.…”
Section: Methodsmentioning
confidence: 99%